Discovery Learning Model: A Solution to Improve Learners' Mathematical Generalization Ability - Arto, Mugi; Linuhung, Nego; Anwar, Rahmad Bustanul (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Mathematical generalization ability is an aspect that students must master in mathematics. This study aims to analyze the effectiveness of the application of the discovery learning model on students' mathematical generalization ability. This research uses a quantitative approach with experimental methods, using a quasi-experimental design with a non-equivalent control group design. The research sample consisted of two classes in one of the high schools in Indonesia, Data were collected through pretest and posttest tests, and analyzed using normality test, homogeneity test, and t-test. The normality test used SPSS with Kolmogorov-Smirnov. The results of the analysis presented show that the pretest and posttest data in the experiment are normally distributed, it can be seen that the significance value of the pretest of the experimental class and the control class is 0.44. this shows that the significance value> 0.05 which means Ho is accepted. The results showed that there was a significant increase in students' mathematical generalization ability in the experimental class compared to the control class. The average posttest score of the experimental class is higher than the control class, indicating that the discovery learning model helps students understand mathematical concepts better through independent exploration and analysis. Thus, it can be concluded that the discovery learning model is effective in improving students' mathematical generalization ability, and can be an alternative learning method that is more interactive and innovative in teaching mathematics.